A study on plea bargaining against theories of punishment and criminal justice / Abdul Hakeem Putra Abdul Rahman Putra, Ahmad Solehin Abd. Ghani, and Amee Asraaf Khairee Amin. - Abdul Rahman Putra, Abdul Hakeem Putra; Abd. Ghani, Ahmad Solehin; Amin, Amee Asraaf Khairee (2011)
On December 13, 2010, it was reported that a change in the Malaysian Criminal Procedure Code to include the concept of formal plea bargaining in criminal cases would soon be implemented by the court. According to the former Chief Justice Yang Amat Arif Tun Tan Sri Dato' Sri Zaki Azmi, the plea bargaining have already put into practice now but this will become a more formal and standard procedure under the amendment. Plea bargaining will only be offered within 30 days after a person has been charged, and the case would go to a full trial after 90 days if no agreement has been reached. Plea bargains will be an option in cases involving first-time offenders including for offenses for which the maximum penalty is death. However, if there is a minimum sentence for the offense, a lesser term will not be available. The Deputy Public Prosecutor will be able to determine whether or not to offer plea bargains in each case. Plea bargaining may also involve a reduction of the charges. It will be the duty of the court to ensure that the plea bargain was entered into voluntarily by the parties. Judges will be able to call the accused in camera to ensure that this has occurred. Once a sentence has been determined neither the prosecution nor the defence will be able to appeal the decision, except on technical grounds. The Chief Justice said that the concept of formal plea bargaining would expedite the disposal of criminal cases and reduce the backlog in the courts. However, we also need to consider certain hidden danger on the application of the plea bargaining in Malaysia. This research will examine the issues pertaining whether the implementation of plea bargaining will fulfilled the theories of punishment and uphold criminal justice or it will be vice versa.